2000
DOI: 10.1128/jvi.74.20.9586-9593.2000
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of the Equine Arteritis Virus Helicase Suggests a Close Functional Relationship between Arterivirus and Coronavirus Helicases

Abstract: The arterivirus equine arteritis virus nonstructural protein 10 (nsp10) has previously been predicted to contain a Zn finger structure linked to a superfamily 1 (SF1) helicase domain. A recombinant form of nsp10, MBP-nsp10, was produced in Escherichia coli as a fusion protein with the maltose-binding protein. The protein was partially purified by affinity chromatography and shown to have ATPase activity that was strongly stimulated by poly(dT), poly(U), and poly(dA) but not by poly(G). The protein also had bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
81
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 64 publications
6
81
0
Order By: Relevance
“…The fact that ATP is a competitive inhibitor of the RTPase reaction catalyzed by SARS helicase suggests that the RNA is hydrolyzed at the same active site used to fuel helicase movement [54]. A similar RTPase that plays a role in CAP formation was also found in the SF1 helicase encoded by bamboo mosaic virus [55] In addition to the SF1 helicase motifs, SARS-CoV nsp13 protein, and its relatives from human coronavirus 229E [56] and equine arteritis virus [57], all contain a cysteine-rich zinc binding domain located at their N-termini. Zinc binding domains have been found linked to other helicases and they are frequently found in proteins that interact intimately with nucleic acids.…”
Section: Sars Coronavirus Helicasementioning
confidence: 98%
“…The fact that ATP is a competitive inhibitor of the RTPase reaction catalyzed by SARS helicase suggests that the RNA is hydrolyzed at the same active site used to fuel helicase movement [54]. A similar RTPase that plays a role in CAP formation was also found in the SF1 helicase encoded by bamboo mosaic virus [55] In addition to the SF1 helicase motifs, SARS-CoV nsp13 protein, and its relatives from human coronavirus 229E [56] and equine arteritis virus [57], all contain a cysteine-rich zinc binding domain located at their N-termini. Zinc binding domains have been found linked to other helicases and they are frequently found in proteins that interact intimately with nucleic acids.…”
Section: Sars Coronavirus Helicasementioning
confidence: 98%
“…Analysis of the distribution of replicase subunits between the cytoplasmic S10 fraction and the RTC-containing P10 fraction revealed that proteins previously implicated in viral RNA synthesis (nsp9-RdRp and nsp10-helicase) (28,29) and DMV formation (nsp2 and nsp3) (30) exclusively cosedimented with the active RTC. In contrast, the main protease nsp4 was found predominantly in the cytosolic S10 fraction and not cosedimenting with RTC activity, suggesting that its presence is not (or, rather, no longer) required for RTC activity.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these replicase subunits appear to become associated with intracellular membranes in the perinuclear region of the infected cell (11)(12)(13), where they are thought to assemble into RTCs. The ORF1b-encoded subunits contain the core enzymatic activities that are involved in viral RNA synthesis, like the RNA-dependent RNA polymerase (RdRp) and RNA helicase (28,29), whereas ORF1a encodes, in addition to the three protease domains, several putative transmembrane subunits. The latter appear to play a more "structural" role by inducing DMV formation (30) and presumably anchoring the RTC to intracellular membranes (11).…”
mentioning
confidence: 99%
“…The ORF1b-encoded polyprotein, which includes the putative RdRp activity and a recently established RNA helicase activity that is associated with a unique zinc finger structure (9,10), is only produced if a ribosomal frameshift from ORF1a into ORF1b takes place during translation (11). This translational strategy is expected to yield two extremely large polyproteins, pp1a and pp1ab, of about 450 and 750 kDa, respectively.…”
mentioning
confidence: 99%